Symbology and Codes in Dan Brown’s Origin - Singh, Raj Kishor (Molung Educational Frontier, 2024)
This paper explores the intricate web of symbology and codes found within Dan Brown's gripping novel, Origin. As a renowned master of blending history, art, science and religion, Brown weaves a tale that captivates readers with a labyrinth of symbols and enigmatic ciphers. Through an analysis of key elements in the narrative, this study aims to shed light on the significance of symbolism and cryptographic puzzles as essential devices in the plot's development. Drawing upon Brown's signature writing style, the paper examines the role of religious symbology, ancient texts and iconic art and architecture, intertwining them with scientific theories to craft a compelling narrative. The central focus lies in the protagonist, Robert Langdon, a symbologist, whose expertise in languages and linguistics plays a pivotal role in deciphering messages and solving the mystery at hand. Jean Moréas' Symbolist Manifesto (1886) is a foundational text in the development of literary symbolism. In this manifesto, Moréas emphasized the importance of symbolism in art and literature, advocating for a departure from naturalism and realism. He proposed that artists should focus on conveying emotions and ideas through symbols, rather than direct representation. Applying Moréas' theory of symbolism, the researcher analyzes how Dan Brown employs symbols and codes as key elements in Origin. By analyzing the relationship between language and technological innovation, the study aims to unveil how these elements converge to heighten the intrigue and suspense in the novel. It delves into the significance of linguistic techniques and cryptic passages, as tools for building suspense and enriching the reading experience. Langdon reveals meanings and ideas inherent in symbols and codes and demystifies the concepts- "Where do we come from?" and "Where are we going?"